اقبال اور آئینہ فردا: چند تحقیقی پہلو: IQBAL AND VISION OF FUTURE: SOME RESEARCH DIMENSSIONS (Al-Aasar, 2025)
Allama Muhammad Iqbal has inspired people with his philosophy, knowledge, understanding of life and wisdom through his poetry and addresses. Also, his thoughts and vision have made an impression on people. These predictions are recognized both nationally and internationally. Many of his predictions have come true. His ideology about feudalism, people living in the east and their standards is also worthwhile. His approach is a true reflection of his future awareness, perseverance and understanding of life. On one side he directs people of the east towards efforts and determination and on the other side he predicts about a new ray of hope, a new life and a new beginning. There are different segments, areas and philosophy that covers his ideology, but in this research article, our focus is only on some aspects of his ideology and vision.